1996
DOI: 10.1177/001872679604900705
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Commitment Across Cultures: The Impact of Antecedents on Korean Employees

Abstract: This study analyzed whether demographic and situational factors identified in the U.S.-based literature had the same antecedent influence on the commitment of 1192 employees in 27 large Korean firms. Consistent with U.S. studies, the Korean employees' position in the hierarchy, tenure in their current position and age all were significantly related to organizational commitment. Total tenure and education were not related. As for the situational antecedents, except for management style, all the others were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
6
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 29 publications
12
80
6
2
Order By: Relevance
“…Sommer et al (1996) revealed that position, tenure and age were significantly related to employee commitment for korean subjects, which were consistent with the western results. Mitchell (2000) suggests that several factors account for generational differences in the attitudes and behaviour of workers.…”
Section: Leadership Type Theoretical Bases --------------------------supporting
confidence: 89%
“…Sommer et al (1996) revealed that position, tenure and age were significantly related to employee commitment for korean subjects, which were consistent with the western results. Mitchell (2000) suggests that several factors account for generational differences in the attitudes and behaviour of workers.…”
Section: Leadership Type Theoretical Bases --------------------------supporting
confidence: 89%
“…We controlled for the proportion of family wealth invested in the family business using four discrete categories (< 25%; 25%-49%; 50%-74%; 75%-100%) because having greater investments may affect family members' motivation and commitment (Chen & Hsu, 2009). In the context of non-family firms, firm size has been shown to have a negative effect on organizational commitment, because as organizations become larger it is more difficult to be visible and feel engaged (Sommer, Bae, & Luthans, 1996). However, in family firms, the opposite may be true for family members as their visibility, power, and attraction to the firm may increase when the family enterprise is of a substantial size.…”
Section: Control Variablesmentioning
confidence: 99%
“…Organizational commitment and age have been found to be positively related in a number of studies Glisson and Durick, 1988;Kushman, 1992;Mathieu and Zajac, 1990;Meyer and Allen, 1984;Meyer et al, 2002;Morris and Sherman, 1981;Newstrom, 2007;Salami, 2008;Sharma and Singh, 1991;Sommer et al, 1996;Suliman and Iles, 2000). However, not all studies have confirmed the relationship of age with organizational commitment (Camilleri, 2002;Chugtai and Zafar, 2006;Iqbal, 2010;Kwon and Banks, 2004).…”
Section: Age and Tenure As Antecedents Of Organizational Commitmentmentioning
confidence: 99%
“…Long-service employees also develop affective attachment to their organization. Therefore they tend to be more committed to the organization (Bosman, Buitendach, and Laba, 2005;Iqbal, 2010;Mathieu and Zajaz, 1990;Meyer and Allen 1984;Meyer et al, 1993;Meyer et al, 2002;Mottaz, 1988;Mowday et al, 1982;Newstrom, 2007;Reichers, 1985;Sommer et al, 1996;Suliman and Lles, 2000).…”
Section: Age and Tenure As Antecedents Of Organizational Commitmentmentioning
confidence: 99%